2021
DOI: 10.3390/ijerph18052260
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Menstrual Health Literacy in Low, Middle and High-Income Countries: A Narrative Review

Abstract: Background: Poor menstrual health literacy impacts adolescents’ quality of life and health outcomes across the world. The aim of this systematic review was to identify concerns about menstrual health literacy in low/middle-income countries (LMICs) and high-income countries (HICs). Methods: Relevant social science and medical databases were searched for peer-reviewed papers published from January 2008 to January 2020, leading to the identification of 61 relevant studies. Results: A thematic analysis of the data… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 73 publications
4
49
0
8
Order By: Relevance
“…So far, only one research is published by using the nationally representative 2014 BDHS data which explored the basic socio-demographic factors associated with the MR service use. This is line of the other studies conducted in LMICs (Holmes K et al, 2021; Chae et al, 2017). However, as far know no research has been conducted yet in Bangladesh to current level of knowledge on MR service use.…”
Section: Introductionsupporting
confidence: 92%
“…So far, only one research is published by using the nationally representative 2014 BDHS data which explored the basic socio-demographic factors associated with the MR service use. This is line of the other studies conducted in LMICs (Holmes K et al, 2021; Chae et al, 2017). However, as far know no research has been conducted yet in Bangladesh to current level of knowledge on MR service use.…”
Section: Introductionsupporting
confidence: 92%
“…School presenteeism and absenteeism may have a long-lasting impact on women’s and PWM’s educational attainment, social and economic participation, and ultimately health outcomes [ 71 , 72 ]. Other studies have assessed productivity loss in the workplace due to menstrual-related issues [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it suggests that some minimal information has been provided in time. A large body of qualitative research has consistently found that participants felt underprepared, and report experiencing high levels of fear and distress at menarche if they are unaware of menstruation ( 15 21 ). Indeed, this was reported as the most consistent finding across 76 included studies in a systematic review of qualitative research on menstrual experiences in low-and middle-income countries ( 15 ).…”
Section: Introductionmentioning
confidence: 99%